Consequences of ignoring dispersal variation in network models for landscape connectivity. Issue 3 (2nd February 2021) - Sullivan, Lauren L.; Michalska‐Smith, Matthew J.; Sperry, Katie P.; Moeller, David A.; Shaw, Allison K.
Abstract: Habitat loss and fragmentation can negatively influence population persistence and biodiversity, but the effects can be mitigated if species successfully disperse between isolated habitat patches. Network models are the primary tool for quantifying landscape connectivity, yet in practice, an overly simplistic view of species dispersal is applied. These models often ignore individual variation in dispersal ability under the assumption that all individuals move the same fixed distance with equal probability. We developed a modeling approach to address this problem. We incorporated dispersal kernels into network models to determine how individual variation in dispersal alters understanding of landscape‐level connectivity and implemented our approach on a fragmented grassland landscape in Minnesota. Ignoring dispersal variation consistently overestimated a population's robustness to local extinctions and underestimated its robustness to local habitat loss. Furthermore, a simplified view of dispersal underestimated the amount of habitat substructure for small populations but overestimated habitat substructure for large populations. Our results demonstrate that considering biologically realistic dispersal alters understanding of landscape connectivity in ecological theory and conservation practice. Abstract : Article impact statement : Including biologically meaningful dispersal in network models alters understanding of connectivity between fragmented habitat patches. Abstract : Consecuencias de la Omisión de la Variación en la Dispersión en los Modelos de Redes para la Conectividad de Paisajes Resumen: La pérdida y la fragmentación del hábitat pueden influir negativamente la persistencia de poblaciones y biodiversidad. Sin embargo, estos efectos pueden ser mitigados si las especies tienen una dispersión exitosa entre los fragmentos aislados de hábitat. Los modelos de redes son la herramienta principal para la cuantificación de la conectividad del paisaje, no obstante en la práctica, se tiende a usar una visión excesivamente simplista de la dispersión de especies. Es común que estos modelos ignoren la variación que existe entre individuos en sus habilidades de dispersión y que asuman que todos los individuos se pueden mover la misma distancia y con la misma probabilidad. En este estudio, desarrollamos una estrategia de modelaje para (minimizar o aminorar) estas limitaciones incorporando kernels de dispersión dentro de los modelos de redes para determinar cómo la variación individual de la dispersión altera el entendimiento de la conectividad a nivel de paisaje. Como un ejemplo, implementamos esta estrategia en un paisaje de pastizal fragmentado en Minnesota. Omitir la variación en la dispersión generó una sobreestimación sistemática de la robustez de la población ante las extinciones locales y una subestimación de la robustez ante la pérdida local del hábitat. Además, una visión simplificada de la dispersión subestimó la complejidad de hábitat para las poblaciones pequeñas, sin emgargo sobreestimó la complejidad para las poblaciones grandes. Nuestros resultados demuestran que incorporar parámetros que describan una dispersión biológica realista tiene implicaciones importantes en la teoría de conectividad de paisajes e implementación de practicas de conservación. 摘要: 生境丧失和破碎化会对种群续存和生物多样性产生负面影响, 但如果物种成功扩散到孤立的栖息地斑块, 则可以缓解这种影响。网络模型是量化景观连接度的主要工具, 但在实际应用中, 物种扩散往往被过度简化。这些模型通常假设所有个体以相同的概率移动相同的固定距离, 而忽略了个体扩散能力的变异。本研究开发了一种建模方法来解决这个问题。我们在网络模型中加入了个体扩散函数, 以确定个体扩散能力差异如何改变对景观尺度连接度的理解, 并把我们的方法应用在明尼苏达州的一个破碎化的草原景观中。结果显示, 忽略个体扩散的变异会导致高估种群产生局部灭绝的稳健性, 且低估种群应对局部栖息地丧失能力的稳健性。此外, 简化扩散模型还会低估小种群栖息地亚结构的数量, 并高估大种群栖息地亚结构数量。我们的研究结果表明, 考虑生物学上实际的扩散能力, 可以改变生态学理论和保护实践中对景观连接度的认识。【翻译: 胡怡思; 审校: 聂永刚】